Eogyropsylla sedzimiri sp. nov. from Eocene Baltic amber with a key to the species of the fossil genus Eogyropsylla Klimaszewski, 1993 (Hemiptera: Sternorrhyncha: Psylloidea) - Drohojowska, Jowita (Zootaxa, 2011)
A new species, Eogyropsylla sedzimiri sp. nov. from Eocene Baltic amber is described. Illustrations of head, thorax, forewing, hind wing, antennae, legs and female terminalia are given. A key to the species of the fossil genus Eogyropsylla Klimaszewski, 1993 is also provided.